480PSafety and efficacy of dacomitinib for EGFR+ NSCLC in the subgroup of Asian patients from ARCHER 1050. (24th November 2019) - Mok, T S K; Cheng, Y; Zhou, X; Lee, K H; Nakagawa, K; Niho, S; Rosell, R; Linke, R; Wong, C H; Tang, Y; Singh, M; Wilner, K D; et al.
Abstract: Background: In the ongoing phase 3 comparison of dacomitinib (daco) and gefitinib (gef) (ARCHER 1050; NCT01774721) as first-line therapy for EGFR-mutation-positive (EGFR+) advanced NSCLC, daco was associated with significant improvement in progression free survival (PFS) and overall survival (OS). Here we present results for the subset of Asian patients (pts). Methods: Eligible pts with newly diagnosed stage IIIB/IV or recurrent EGFR+ advanced NSCLC were randomized (1:1) to oral daco 45 mg once daily or gef 250 mg. Randomization was stratified by race and EGFR mutation (exon 19 del/exon 21 L858R) status. The primary efficacy endpoint was PFS by blinded independent radiologic central review (BIRC). Secondary endpoints were OS, objective response rate (ORR) and duration of response (DOR) by BIRC, and safety. Results: Of 346 Asian pts, 170 were randomized to daco treatment and 176 to gef. Demographics and baseline characteristics of the groups were well balanced. At the July 29, 2016 data cutoff, the hazard ratio for PFS was 0.510 (95% confidence interval [CI] 0.392, 0.664), favoring daco (2-sided p value < 0.0001). Median PFS was 16.5 months (95% CI 12.9, 18.4) for daco and 9.3 months for gef (95% CI 9.2, 11.0). OS, ORR and DOR are shown in the table. Treatment-related adverse events (TRAEs) occurring in ≥ 50% of daco-treated pts were diarrhea (88.2%), paronychia (64.7%), and dermatitis acneiform (56.5%). In the gef arm, diarrhea (52.3%) was the only TRAE that occurred in ≥ 50% of pts. The daco dose was reduced in 67.6% of pts associated with adverse events (AEs); gef dose was reduced to every other day dosing in 9.7% of pts associated with AEs. Conclusions: First-line daco was associated with significant prolongation of PFS compared with gef in Asian pts with EGFR+ advanced NSCLC. Daco treatment showed improved OS, ORR, and DOR compared to gef treatment. The AE profile for daco and gef in Asian pts was consistent with the overall ARCHER 1050 study. Clinical trial identification: NCT01774721. Editorial acknowledgement: Medical writing support was provided by Michelle Daniels (inScience Communications, Springer Healthcare, Philadelphia, PA, USA). Legal entity responsible for the study: Pfizer Inc. Funding: Pfizer Inc. Disclosure: T.S.K. Mok: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: ACEA Pharma; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Alpha Biopharma Co., Ltd.; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Amgen; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Amoy Diagnostics Co., LTD.; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, before 1/1/19: AstraZeneca; Honoraria (self), Advisory / Consultancy: Bayer; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: BI; Honoraria (self), Advisory / Consultancy: Blueprint Medicines Corporation; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): BMS; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy: CStone Pharmaceuticals; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Honoraria (self), Advisory / Consultancy: Fishawack Facilitate Ltd; Honoraria (self), Advisory / Consultancy: Hengrui Therapeutics Inc.; Honoraria (self), Advisory / Consultancy: Ignyta, Inc.; Honoraria (self), Advisory / Consultancy, Sept 2019: Incyte Corporation; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: InMed Medical Communication; Honoraria (self), Advisory / Consultancy, Jun 2019: IQVIA; Honoraria (self), Advisory / Consultancy: Janssen; Honoraria (self), Advisory / Consultancy: Loxo-Oncology; Honoraria (self), Advisory / Consultancy: Merck Serono; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): MSD; Honoraria (self), Advisory / Consultancy: MoreHealth; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Honoraria (self), Advisory / Consultancy: OncoGenex Pharmaceuticals, Inc.; Honoraria (self), Advisory / Consultancy: OrigiMed; Honoraria (self), Advisory / Consultancy: PeerVoice; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Pfizer; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: PrIME Oncology; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche/Genentech; Honoraria (self), Advisory / Consultancy: Sanofi-Aventis R&D; Honoraria (self), Advisory / Consultancy: SFJ Pharmaceutical Ltd.; Honoraria (self), Advisory / Consultancy: Takeda Pharmaceuticals HK Ltd.; Honoraria (self), Advisory / Consultancy: Vertex Pharmaceuticals; Honoraria (self), Advisory / Consultancy: Yuhan Corporation; Advisory / Consultancy: Cirina; Advisory / Consultancy, uncompensated: geneDecode Co., Ltd.; Speaker Bureau / Expert testimony: Taiho; Speaker Bureau / Expert testimony: Takeda Oncology; Leadership role, Officer / Board of Directors, Remunerated: AstraZeneca PLC; Leadership role, Officer / Board of Directors, Remunerated: Hutchison Chi-Med; Leadership role, Officer / Board of Directors, Non-remunerated: American Society of Clinical Oncology; Leadership role, Officer / Board of Directors, Non-remunerated: Asian Thoracic Oncology Research Group; Leadership role, Officer / Board of Directors, Non-remunerated: Chinese Lung Cancer Research Foundation Limited; Leadership role, Officer / Board of Directors, Non-remunerated: Chinese Society of Clinical Oncology; Leadership role, Officer / Board of Directors, Non-remunerated: Hong Kong Cancer Fund; Leadership role, Officer / Board of Directors, Non-remunerated: Hong Kong Cancer Therapy Society; Leadership role, Officer / Board of Directors, term ended on 30/4/19: International Association for the Study of Lung Cancer ; Research grant / Funding (institution): Clovis Oncology; Research grant / Funding (institution): Roche; Research grant / Funding (institution): SFJ; Research grant / Funding (institution): XCovery; Shareholder / Stockholder / Stock options, Shareholder: Hutchison Chi-Med; Shareholder / Stockholder / Stock options, Shareholder: Sanomics Ltd.; Shareholder / Stockholder / Stock options, now Biolidics Ltd.; Stock option: Clearbridge Biomedics; Shareholder / Stockholder / Stock options, Stock option: Loxo-Oncology; Shareholder / Stockholder / Stock options, Stock option: OrigiMed Co. Ltd.; Shareholder / Stockholder / Stock options, Stock option: Virtus Medical Group; Research grant / Funding (institution): AstraZeneca. K.H. Lee: Advisory / Consultancy: MSD; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: BMS. K. Nakagawa: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Astellas Pharma Inc.; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Takeda Pharmaceutical Co., Ltd; Honoraria (self), Research grant / Funding (institution): AstraZeneca K.K.; Honoraria (self), Research grant / Funding (institution): Chugai Pharmaceutical Co., Ltd.; Honoraria (self), Research grant / Funding (institution): MSD K.K.; Honoraria (self), Research grant / Funding (institution): Eli Lilly Japan K.K.; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical Co., Ltd.; Honoraria (self), Research grant / Funding (institution): Nippon Boehringer Ingelheim Co., Ltd.; Honoraria (self), Research grant / Funding (institution): Daiichi Sankyo Co., Ltd.; Honoraria (self), Research grant / Funding (institution): Novartis Pharma K.K.; Honoraria (self), Research grant / Funding (institution): Taiho Pharmaceutical Co., Ltd.; Honoraria (self), Research grant / Funding (institution): Pfizer Japan Inc.; Honoraria (self), Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (self): Nikkei Business Publications, Inc.; Honoraria (self): Kyorin Pharmaceutical Co., Ltd.; Honoraria (self): Medicus Shuppan, Publishers Co., Ltd.; Honoraria (self): CareNet, Inc.; Honoraria (self): Thermo Fisher Scientific K.K.; Honoraria (self): Nichi-Iko Pharmaceutical Co., Ltd.; Honoraria (self): Nanzando Co., Ltd; Honoraria (self): Hisamitsu Pharmaceutical Co., Inc; Honoraria (self): Medical Review Co., Ltd.; Honoraria (self): Yodosha Co., Ltd; Honoraria (self): Yomiuri Telecasting Corporation; Research grant / Funding (institution): ICON Japan K.K.; Research grant / Funding (institution): Quintiles Inc.; Research grant / Funding (institution): CMIC Shift Zero K.K.; Research grant / Funding (institution): Eisai Co., Ltd.; Research grant / Funding (institution): Parexel International Corp.; Research grant / Funding (institution): Kissei Pharmaceutical Co., Ltd.; Research grant / Funding (institution): IQVIA; Research grant / Funding (institution): Kyowa Hakko Kirin Co., Ltd; Research grant / Funding (institution): EPS Corporation; Research grant / Funding (institution): SymBio Pharmaceuticals Limited; Research grant / Funding (institution): Bayer Yakuhin, Ltd; Research grant / Funding (institution): Merck Serono Co., Ltd.; Research grant / Funding (institution): A2 Healthcare Corp.; Research grant / Funding (institution): AbbVie Inc. . S. Niho: Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Pfizer; Honoraria (self): Chugai; Honoraria (self): Taiho; Honoraria (self), Research grant / Funding (institution): MSD; Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Research grant / Funding (institution): Eli Lilly; Honoraria (self): Novartis; Honoraria (self): Boehringer Ingelheim; Research grant / Funding (institution): Merck Serono. R. Linke: Full / Part-time employment: SFJ Pharmaceuticals ® . C.H. Wong: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. Y. Tang: Full / Part-time employment: Pfizer Inc. M. Singh: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. K.D. Wilner: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer Inc. Y-L. Wu: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self): Eli Lilly; Honoraria (self): Pfizer; Honoraria (self): MSD; Honoraria (self): BMS. All other authors have declared no conflicts of interest.